Conversion to mammalian target of rapamycin inhibitors increases risk of de novo donor‐specific antibodies. (22nd May 2014) - Croze, Laure‐Emmanuelle; Tetaz, Rachel; Roustit, Matthieu; Malvezzi, Paolo; Janbon, Bénédicte; Jouve, Thomas; Pinel, Nicole; Masson, Dominique; Quesada, Jean‐Louis; Bayle, François; Zaoui, Philippe
Summary In kidney transplantation, conversion to mammalian target of rapamycin (mTOR) inhibitors may avoid calcineurin inhibitor (CNI) nephrotoxicity, but its impact on post‐transplant allo‐immunization remains largely unexplored. This retrospective cohort study analyzed the emergence of donor‐specific antibodies (DSA) in kidney transplant recipients relative to their immunosuppressive therapy. Among 270 recipients without pretransplant immunization who were screened regularly for de novo DSA, 56 were converted to mTOR inhibitors after CNI withdrawal. DSA emergence was increased in patients who were converted to mTOR inhibitors (HR 2.4; 95% CI 1.06–5.41, P = 0.036). DSA were mainly directed against donor HLA‐DQB1 antigens. The presence of one or two DQ mismatches was a major risk factor for DQ DSA (HR 5.32; 95% CI 1.58–17.89 and HR 10.43; 95% CI 2.29–47.56, respectively; P < 0.01). Rejection episodes were more likely in patients converted to mTOR inhibitors, but this difference did not reach significance (16% vs. 7.9%, P = 0.185). Concerning graft function, no significant change was observed one year after conversion (P = 0.31). In conclusion, conversion to mTOR inhibitors may increase the risk of developing class II DSA, especially in the presence of DQ mismatches: this strategy may favor chronic antibody‐mediated rejection and thus reduce graft survival.